2019
DOI: 10.3390/su11041192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality Traits and Entrepreneurship Education on Entrepreneurial Intentions of Business and Engineering Students

Abstract: Entrepreneurs bring an enormous contribution to a country’s economic growth. Developing individual’s interest into new venture creation represents an important asset, especially for less developed countries where entrepreneurial activities are fundamental in enhancing economic growth. The recent economic crisis turned the attention of European policymakers towards entrepreneurship as a driving force for the creation of new job opportunities, regional/national competitiveness and growth. The aim of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(233 citation statements)
references
References 97 publications
16
150
2
7
Order By: Relevance
“…Several studies have shown that successful entrepreneurs have an internal locus of control compared to ordinary people (Aboal & Veneri, 2016;Antoncic et al 2015;Brockhaus, 1982;Chaudary, 2017). Moreover, other studies authenticate the positive relationship between internal locus of control and entrepreneurship intentions (Dinis et al, 2013;Vodă & Nelu, 2019). The interpretation drawn from these findings is that a high internal locus of control allows entrepreneurs to withstand disappointments and setbacks, and thus persevere.…”
Section: Locus Of Controlmentioning
confidence: 54%
“…Several studies have shown that successful entrepreneurs have an internal locus of control compared to ordinary people (Aboal & Veneri, 2016;Antoncic et al 2015;Brockhaus, 1982;Chaudary, 2017). Moreover, other studies authenticate the positive relationship between internal locus of control and entrepreneurship intentions (Dinis et al, 2013;Vodă & Nelu, 2019). The interpretation drawn from these findings is that a high internal locus of control allows entrepreneurs to withstand disappointments and setbacks, and thus persevere.…”
Section: Locus Of Controlmentioning
confidence: 54%
“…In the last years, many researchers have studied the importance of this phenomenon considering three main perspectives: the economic factors [3,8,10], the socio-cultural factors [5,11], and perception determinants [8,[12][13][14][15]]. Yet, several previous studies found some mixed results about the relationships between some perceptual variables and entrepreneurial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among Chinese engineering students, Fang and Chen [12] suggested that a subjective approach to entrepreneurship education can enrich entrepreneurial intentions. In Romania, a study conducted by Voda and Florea [13] reported that the locus of control, need for achievement, and entrepreneurial education are the key determinants for entrepreneurial intention among university students. A study by Paunescu, Popescu, and Duennweber [14] reported that the feasibility, social stability, income, education, and working status affect entrepreneurial intention among Romanians.…”
Section: Introductionmentioning
confidence: 99%